4CPS-012 Audit of oral anticoagulant prescribing; what has changed in 4 years?. (24th March 2020) - Tuthill, J; Kieran, M; Ging, P; Meegan, C
Abstract : Background and importance: The Mater Misericordiae University Hospital (MMUH) formulary recommendations for oral anticoagulants (OACs) are in line with the Health Service Executive (HSE) Medicines Management Programme. 1 2 Warfarin is the OAC of choice. Apixaban is the preferred direct oral anticoagulant (DOAC) if warfarin is unsuitable. Edoxaban, dabigatran and rivaroxaban are third-line options. 1 2 In 2014, warfarin was prescribed in 81% of cases in the MMUH. National data indicate DOACs are now prescribed more often than warfarin. 2 Aim and objectives: To identify current MMUH OAC prescribing practice and compare results with 2014 data. Material and methods: A point prevalence audit was completed in November 2018 by clinical pharmacists, across 30 wards on all patients receiving OACs. The OAC, indication, dose, prescribing team speciality and if treatment was commenced on this MMUH admission were recorded. Results were collated, analysed and compared with an identical 2014 audit. Results: More MMUH patients were prescribed OACs in 2018 (n=87) than in 2014 (n=53) (p<0.01). Apixaban was the most commonly prescribed OAC (48%), followed by rivaroxaban (20%), warfarin (16%), dabigatran (14%) and edoxaban (2%). In 2014, warfarin was the most commonly prescribed OAC (81%), followed by rivaroxaban (15%), apixaban (2%) and dabigatran (2%). DOAC prescribing was mainly for licensed indications and doses. Medicines for the elderly speciality had the most patients on OACs in both 2018 (n=29) and 2014 (n=14). The majority of patients prescribed OACs in both 2014 and 2018 were aged 60 years or over. In 2014, all patients <60 years of age requiring oral anticoagulation were on warfarin. In 2018, all these patients were on DOACs. The number of patients starting OACs during MMUH admission was almost 10% higher in 2018 (n=27) than in 2014 (n=11) (p=0.18). Conclusion and relevance: Apixaban was the most commonly prescribed OAC in the MMUH. Use of warfarin has decreased from 81% in 2014 to 16% in 2018 and is now surpassed by DOAC prescribing (p<0.01). Increased OAC prescribing means increased pharmacy workload in terms of medication review and patient education. References and/or acknowledgements: 1. MMUH. Prescriber's guide, chapter 5.8. Information on DOACs. Last updated December 2018. 2. HSE. Oral anticoagulants for stroke prevention in non-valvular atrial fibrillation. V.1.1. Medicines Management Programme. Updated September 2018. No conflict of interest.